Stimulation of the thalamus and its effect on electrographic manifestations of the brain in unrestrained rats - Chocholová, L; Kolínová, M; Fischer, J (Physiologia Bohemoslovaca, 1977)
The thalamus was electrically stimulated in unrestrained rats with implanted cortical and subcortical electrodes. Single pulses often triggered rhythmic cortical activity identical with the 8--9/sec spike episodes which occur spontaneously in rats in the walking state. In rhythmic stimulation of the thalamus, self-sustained 3/sec spike-wave paroxysmal activity, with partial clonic jerks, was observed. Specific and non-specific thalamic nuclei participated in the production of these activities.
Keywords: Rats; Thalamus; Electroencephalography; evokované potenciály; hipokampus; Evoked Potentials; mužské pohlaví; elektroencefalografie; jádra thalamu; mozek; Thalamic Nuclei; Arousal; krysa rodu Rattus; Brain; mozková kůra; zvířata; Cerebral Cortex; elektrická stimulace; thalamus; Electric Stimulation; arousal; Male; Hippocampus; Animals